(3GdEHJgGL aj TQM GdENJdGLs
(3ChdgG (B:s
(3hHYO agPG cJGH GdEHJgGL ai TQM GdENJdGL Ydi SJ ebGdGJ s
(3BNQgG (B:s
(3bGd GdUGOb (B: (3hGdLejY jeQV bdjdkG hjHQC HEPf Gddg JYGdi hGddg Gdehab s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B137 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQGSI (B23) s
Keywords: (3GdaQGSIs